Determinants of waqf institutions’ efficiency in Malaysia / Azrizal Husin - Husin, Azrizal (2021)
Waqf is a unique form of philanthropy in Islam with the objectives of providing spiritual rewards the donor (or waqif) continuously in this World and Hereafter, as well as to enhance the ummah’s (society) standard of living according to Islamic principles. It is estimated that the global Waqf assets are valued at US$1 trillion, while in Malaysia, it has the potential to be as high as US$ 325.4 billion. Waqf institutions are trusted bodies that manage Waqf in many Muslim countries. In Malaysia, Waqf is managed by the State Islamic Religious Councils (SIRCs) which are responsible to ensure that the Waqf assets and its objectives are managed efficiently by producing a maximum level of outputs given a certain level of inputs or minimize inputs given a certain level of outputs. In this study, the efficiency of Waqf institutions in Malaysia during the 2010 to 2016 period was analyzed through a two-stage analysis. In the first stage, the DEA Windows Analysis method was deployed to gauge the efficiency levels of the Waqf institutions, while in the second stage, the Pooled Ordinary Least Square (OLS) Regression Model was deployed to examine the Waqf-specific characteristics, macroeconomic conditions, and regulatory determinants on the efficiency of the Waqf institutions in Malaysia. The findings of the first stage analysis recommended that the efficiency of the Waqf institutions in Malaysia was underperforming and unfit to carry out its main functions efficiently. Furthermore, it was also discovered that the Scale Efficiency (SE) was more dominant over the Pure Technical Efficiency (PTE) in determining the technical efficiency of the Waqf institutions in Malaysia, which technically suggested that the inefficiency of Waqf institutions in Malaysia might be mainly caused by managerial inefficiency. In the second stage, it was discovered that the efficiency was influenced significantly by the Number of Employees (NOE), Size of Waqf Lands Under Management (SWLUM), Number of Branches available (NOB), Existence of Waqf Operational Websites (WEB), Number of Social Media adopted (SM), Economic Growth (GDP), Corporatization (CORP), and Board Size (BS). Overall, the findings of this study highlighted the importance of ensuring efficiency of Waqf institutions in Malaysia. Furthermore, relevant authorities, especially the SIRCs, the Department of Zakat, Waqaf, and Haji (JAWHAR), and the government ought to deploy efficiency enhancement measures of Waqf institutions as well as strengthening the collaborations between authorities and stakeholders in ensuring the noble objectives of Waqf institutions in Malaysia are successfully accomplished.